Changes in land use typology of global airports: An empirical investigation with implications for the aerotropolis concept. (December 2021) - Kamruzzaman, Md.; Aston, Laura; Baker, Douglas; Braun, Boris; Shatu, Farjana
Abstract: Aerotropolis is an urban development concept characterised by the concentration of land uses fostering economic activities around airports. However, limited empirical evidence exists about the formation of aerotropolises and their effects on the productivity of airports. This study addresses the gaps by examining changes in land use patterns around 75 major airports globally, using data extracted from Google Earth for two time periods: 2004 and 2014. A Two-Step cluster analysis technique was applied to identify natural groupings of the airports in terms of their land use patterns for both periods. Changes in cluster membership were observed between the periods to examine the process of aerotropolis formation. A multivariate multiple linear regression (MMLR) model is estimated to identify factors contributing to aerotropolis formation process. Finally, the effects of the aerotropolis formation process on airport productivity is estimated in a two-stage least square (2SLS) regression model. Cluster analysis results show that airport land side development can be classified into three groups: Island airports (surrounded by largely vacant land), Waterfront airports (adjacent to a large body of water), and Built form airports (well-developed residential, commercial and industrial land uses). Overall, built-up areas increased by 2.1% between 2004 and 2014, and only three airports transitioned from Island to Built form – suggesting a weak evidence of the aerotropolis formation process. Developable land surrounding the airports and city population growth rate contributed significantly to this process, which consequently contributed to the productivity of airports. In conclusion, aerotropolises are a promising concept, yet unreal. It needs to be integrated with city plans to direct development, and thereby, to make it a reality. Highlights: Empirical investigation of the airport landside development for 75 airports in 2004 and 2014. Spatial examination of the aerotropolis formation process Develops three typology of landside development (Built form, Waterfront, and Island). Found weak evidence of 'growing aerotropolis' and 'reinforcing aerotropolis'. Aerotropolis formation process increases productivity of airports.